KUALITAS SISTEM INFORMASI DAN KEPUASAN PENGGUNA SISTEM INFORMASI PERGURUAN TINGGI UNIVERSITAS SYIAH KUALA - Mirna Indriani; Reza Adryan (Jurnal Telaah dan Riset Akuntansi, 2009)
The purpose of this research was to examine the effect of Information system quality; reliability, ease of use, flexibility, functionality, to user satisfaction. Responsees were collected from 392 user in three groups;  lectures, operator system information and students of economics faculty  universitas Syiah Kuala. The research hypotheeses were analyzed using multiple regresion.The result show reliability,  flexibility, and functionality  have strong influence   on user satisfaction. While variable  ease of use  doesn’t influence  on    user satisfaction. Keywords: information system; quality, reliability, ease of use, flexibility, functionality, and user satisfaction.